2013
DOI: 10.1007/s00066-013-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Radio-induced apoptosis of peripheral blood CD8 T lymphocytes is a novel prognostic factor for survival in cervical carcinoma patients

Abstract: For the first time, RIA in CD8 T lymphocytes was demonstrated to be a predictive factor for survival in cervical carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Lymphocytes, in particular, appear to be the ideal candidates for such analyses, owing to both their accessibility and high concentrations in peripheral blood ( Azria et al, 2012 ). As previously reported, though only in a retrospective manner or in prospective single-Institute studies ( Ordonez et al, 2014 , Ozsahin et al, 2005 , Azria et al, 2008 , Bordon et al, 2010 , Foro et al, 2014 ) an inverse relationship between the percentage of apoptosis in irradiated lymphocytes and late toxicity emerged also in this report ( Azria et al, 2015 ). The mechanism of this inverse association is not completely clear, being possibly related to the delay of cells in recognizing the radiation-induced cell damage and initiating apoptosis, with a consequently increased risk of toxicity and, theoretically, of cancer radioresistance and reduced tumor control.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Lymphocytes, in particular, appear to be the ideal candidates for such analyses, owing to both their accessibility and high concentrations in peripheral blood ( Azria et al, 2012 ). As previously reported, though only in a retrospective manner or in prospective single-Institute studies ( Ordonez et al, 2014 , Ozsahin et al, 2005 , Azria et al, 2008 , Bordon et al, 2010 , Foro et al, 2014 ) an inverse relationship between the percentage of apoptosis in irradiated lymphocytes and late toxicity emerged also in this report ( Azria et al, 2015 ). The mechanism of this inverse association is not completely clear, being possibly related to the delay of cells in recognizing the radiation-induced cell damage and initiating apoptosis, with a consequently increased risk of toxicity and, theoretically, of cancer radioresistance and reduced tumor control.…”
supporting
confidence: 80%
“…This is not surprising, given the overall favorable prognosis of the analyzed cohort, in which clinical relapses and deaths occurred in only 2.6% and 1.1%, respectively, of the cases. As emphasized in the paper, breast cancer is of course not the most appropriate cancer in which to evaluate the possible prognostic significance of RILA, which has been demonstrated, on the contrary, in more aggressive neoplasms such as cervical ( Ordonez et al, 2014 ) and prostate carcinoma ( Foro et al, 2014 ), though not confirmed in a prospective Swiss study on 399 patients with miscellaneous cancers ( Ozsahin et al, 2005 ). Undoubtedly, the possible association between the radiosensitivity of normal tissues and clinical outcome deserves further thorough investigation ( Ordonez et al, 2014 ).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We did not observe statistical correlation between RILA and tumor recurrences but the number of events is too small to draw any conclusions. In cancers with higher recurrences like locally advanced prostate ( Foro et al, 2014 ) or cervix ( Ordonez et al, 2014 ), such correlations have recently been suggested but this needs to be confirmed in larger prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Once the relationships between tumor stage, therapy and immune status have been identified, prognostic and predictive markers might be derived [3,4,5]. Thereby, one big challenge is to monitor the immune status in a close-meshed manner to identify optimal time points for integration of IT into existing RT/CT protocols [6].…”
Section: Introductionmentioning
confidence: 99%